Combined Versus Singular Therapy of Coconut (Cocos nucifera L.) Water and Lime (Citrusaurantiifolia L) Juice in Diabetes Control: Impacts, Implications, and Therapeutic Differences - Magnus Michael Chukwudike Anyakudo; Bolatito Morolayo Akinmoju (International Journal of Nutrition, 2025)
This study determined and compared the effects of single and combined therapy of coconut water and lime juice in diabetes control in male diabetic Wistar rats. Twenty eight male Wistar rats (weighing: 150-200g) were induced with diabetes mellitus using alloxan monohydrate solution (150mg/kg) and categorized into four experimental groups (n = 7, each): Diabetic Control (CTR), Diabetic treated with coconut water (CNW), Diabetic treated with coconut water and lime (BLC), Diabetic treated with lime (LMJ). Animals were fed according to the experimental design with water ad libitum for six (6) weeks. Body weights, blood glucose concentrations, glycemic tolerance and lipid profiles were measured and determined during the study. Data was analyzed using Microsoft Excels and Statistical SPSS program version 24. Results are expressed as mean ± SEM. Comparison between groups were made using Students’ t-test and one way ANOVA followed by Multiple Duncan tests. P value < 0.05 was set as significant. Lime juice (πb.wt.- 5.60%, P = 0.003), coconut water (πb.wt.- 30.760%, P = 0.012) and Coco-lime mixture (πb.wt.- 11.10%, P = 0.028) decreased mean body weight gain (πb.wt.) significantly (P < 0.05) compared with the control (πb.wt. - 38.83%). Blood sugar level differentially decreased significantly in all treated groups: CNW (27.03%) > LMJ (19.5%) >> BLC (9.83%). Glycemic tolerance and lipid profile improved significantly with single administration better than combined administration. In conclusion, single administration of coconut water and lime juice differentially improved diabetes control effectively in diabetic rats better than their combined mixture.
Keywords: Coconut water